Re-evaluation of shear strength design code provisions of RC beams with shear reinforcements - Yu, Bo (2022)
This paper provides a critical probabilistic evaluation of shear strength design code provisions for reinforced concrete (RC) beams with shear reinforcements under different strength combinations of steel reinforcements and concrete. Based on the modified compression field theory (MCFT), a probabilistic shear strength model for RC beams with shear reinforcements was proposed by taking into account the influences of contribution ratio for shear strength between concrete and stirrup, constitutive law of cracked concrete, and uncertainty in influencing coefficient of shear reinforcement. Then the accuracy and applicability of three typical shear strength design code provisions under different strength combinations of steel reinforcements and concrete were evaluated based on the confidence interval determined by the proposed probabilistic shear strength model. Meanwhile, the influences of material strength of steel reinforcements and concrete on confidence level of three typical shear strength design code provisions were also investigated. Finally, three typical shear strength design code provisions for RC beams were modified to improve the computational accuracy based on the characteristic values of correction factor under different strength combinations of steel reinforcements and concrete.